Case Report: Metagenomic next-generation sequencing applied in diagnosing psittacosis caused by Chlamydia psittaci infection - Xu, Wan; Wang, Qing; Li, Lin; Zhu, Binghua; Cai, Qingqing; Yi, Xiaoli; Fang, Rong; Wang, Qian (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Chlamydia psittaci is the causative agent of psittacosis in humans, while its rapid identification is hampered due to the lack of specificity of laboratory testing methods.Case presentation: This study reports four cases of C. psittaci infection after contact with a domestic parrot, all belonging to the same family. Common manifestations like fever, cough, headache, nausea, and hypodynamia appeared in the patients.Metagenomic next-generation sequencing (mNGS) aided the etiological diagnosis of psittacosis, revealing 58318 and 7 sequence reads corresponding to C. psittaci in two cases. The detected C. psittaci was typed as ST100001 in the Multilocus-sequence typing (MLST) system, a novel strain initially reported. Based on the results of pathogenic identification by mNGS, the four patients were personalized, treated with different antibiotics, and discharged with favorable outcomes.In diagnosing psittacosis caused by a rare C. psittaci agent, mNGS provides rapid etiological identification, contributing to targeted antibiotic therapy and favorable outcomes. This study also reminds clinicians to raise awareness of psittacosis when encountering family members with a fever of unknown origin.